An Investigation of Ethics Officer Independence - Hoffman, W. Michael (Journal of business ethics, 2008)
In this paper, we examine whether ethics officers are able to perform their assigned duties independently of organizational management. Specifically, we investigate whether inherent conflicts of interest with company management potentially hinder the ability of ethics officers to serve as an effective monitor and deterrent of unethical activity throughout the organization. As part of our analysis, we conducted 10 detailed phone interviews with current and retired ethics officers in order to determine whether practicing ethics officers feel the need for additional independence protection from management. We propose that the current system in which ethics officers report to management must be changed in order for ethics officers to effectively perform their jobs. Specifically, we maintain that ethics officers should (1) be hired by, (2) be fired by, and (3) report directly to the corporate board of directors rather than company management. Such a change in the reporting environment would greatly enhance the independence of ethics officers.